Suplementação de acidificantes em rações de leitões desmamados: Desempenho e digestibilidade - Miguel, Willian Correa; da Trindade Neto, Messias Alves; Berto, Antônio Dirlei [UNESP]; Kobashigawa, Estela; Gandra, Erika Rosendo de Sena [UNESP] (My University, 2011)
In two experimental assays it was evaluated the diet acidifier supplementation effect on performance (assay 1) and on nutrient apparent digestibility coefficients (assay 2). During 42 days in assay 1, 120 piglets weaned at 21-days years old were allotted in8eight experimental block design with3three pigs per experimental unit. The treatments were a control and4four acidified diets. In assay 2,0ten piglets with an average weight of 16,4 kg were allotted in two experimental block design receiving two treatments under five replications (control diet without acidifier or supplied with 1,0% fumaric acid). On performance study the fumaric acid inclusion in the diet permitted a feed intake increase from 0 to 15 days, and weight gain from 0 to 32 days and from 0 to 42 days. In assay 2, the diet 1,0% of fumaric acid inclusion did not modified the apparent digestibility coefficients of dry matter and moreover diet chemical compounds. The similar apparent digestibility coefficient of dietetic nutrients with the acidifier inclusio, probabl, occurred due to the short period of evaluation. The fumaric acid inclusion in weaned piglet diets improved performance of piglets.
Supplementation of acidifiers in diets of weaned pigs: Performance and digestibility
Keywords: Feed:gain ratio; Organic acids; Weaned; Weight gain; Suidae